DETERMINANTS OF SUCCESSFUL INTERNALIZATION OF RELIGIOUS MODERATION IN CHARACTER EDUCATION AT THE PRIMARY SCHOOL LEVEL: A SYSTEMATIC LITERATURE REVIEW - Junaidi; Rohmani Rohmani (International Journal of Multidisciplinary Reseach, 2026)
Background and Purpose: The successful internalization of religious moderation within primary school character education constitutes a multidimensional and contextually embedded process of critical importance for fostering tolerance and social cohesion in pluralistic societies. Despite growing scholarly interest, a rigorous synthesis of the factors determining this success remains absent. This systematic literature review (SLR) aims to identify, critically analyze, and synthesize the key determinants of successful religious moderation internalization in primary school character education programs. Methods: Following the PRISMA 2020 guidelines, a systematic search of the Scopus database was conducted using Boolean operators combining the terms "religious moderation," "character education," "primary school," and "internalization." After screening 278 initially identified records and applying predefined inclusion/exclusion criteria, 25 peer-reviewed articles were selected for qualitative synthesis. Results: Thematic analysis revealed four interrelated determinant clusters: (1) pedagogical approaches and curriculum innovation, including inquiry-based learning, dialogic discussion, storytelling, and local wisdom integration; (2) teacher competence and professional development, encompassing pedagogical proficiency, attitudinal modelling, and sustained training; (3) school climate and external engagement, involving inclusive organizational culture, strong leadership, parental involvement, and community partnerships; and (4) measurement and evaluation, highlighting the need for holistic, validated, multi-domain assessment instruments. Conclusion: Effective religious moderation internalization requires coordinated, systemic action across pedagogical, professional, environmental, and evaluative dimensions. Significant research gaps persist in the areas of longitudinal measurement, digitally responsive curriculum design, and cross-cultural comparative studies.